2005
DOI: 10.1096/fj.04-3621fje
|View full text |Cite
|
Sign up to set email alerts
|

Roles of reactive oxygen species in angiopoietin‐1/tie‐2 receptor signaling

Abstract: In this study we identified the involvement of reactive oxygen species (ROS) in signaling and biological effects of the angiopoietin-1 (Ang-1)/tie-2 receptor pathway. Exposure of human umbilical vein endothelial cells to Ang-1 (50 ng/ml) induced rapid and transient production of ROS, particularly superoxide anions. ROS production was attenuated by preincubation with a peptide (gp91ds-tat) that inhibits the association of the gp91(phox) subunit with the p47(phox) subunit of NADPH oxidase and by the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
105
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 54 publications
4
105
3
Order By: Relevance
“…These data contrast with those of Wu et al (78) who showed that VEGF-mediated phosphorylation of JNK was oxidasedependent. Moreover, previous studies in HUVEC have demonstrated a role for ROS in VEGF-mediated activation of ERK1/2 in HUVEC and porcine aortic endothelial cells (23,36). The reason for the discrepancies between these latter reports and the present study is not clear.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These data contrast with those of Wu et al (78) who showed that VEGF-mediated phosphorylation of JNK was oxidasedependent. Moreover, previous studies in HUVEC have demonstrated a role for ROS in VEGF-mediated activation of ERK1/2 in HUVEC and porcine aortic endothelial cells (23,36). The reason for the discrepancies between these latter reports and the present study is not clear.…”
Section: Discussioncontrasting
confidence: 99%
“…Chen et al (35) demonstrated that Ang1-dependent phosphorylation of Akt at Ser-473 in porcine and murine endothelial cells was dependent on NADPH oxidase-derived ROS. In another study, Ang1-mediated phosphorylation of Akt in HUVEC was unaffected by overexpression of superoxide dismutase, catalase, or dominant-negative Rac1 (Rac1N17) (36). We have found that hepatocyte growth factor-mediated activation of Akt in HCAEC occurs independently of NADPH oxidase activity (supplemental Fig.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Accumulating evidence suggests that high levels of ROS could act as signaling molecules to mediate various growth-related responses, including angiogenesis. It has been reported that VEGF (vascular endothelial growth factor) and angiopoietin-1 (Ang1), two angiogenic growth factors, induce EC migration through an increase in ROS [13,26] . Recently, Zhao et al reported that ROS promote the formation of new vessels in the infracted heart and contribute to cardiac repair [25] .…”
Section: Discussionmentioning
confidence: 99%
“…ROS may play a role as the mediator for the consequence of tumor induced the expression of tumor biomarkers involved tumor angiogenesis. The activation for VEGF and angiopoietin-1 induced EC migration and/or proliferation through an increase in ROS mainly proposed by a number of researchers [28,29] . It was found that ethanol stimulated actin cytoskeletal reorganization, cell motility and tube formation in a ROS-dependent manner in ECs [30] .…”
Section: Discussionmentioning
confidence: 99%